INVESTIGATION OF GRAIN MATERIAL MOVEMENT ON GRAVITATION INSTALLATION TRAYS - Arendarenko, V. M.; Samoilenko, T. V.; Ivanov, О. М. (Scientific Progress & Innovations, 2021)
Various technological operations are widely used at elevator enterprises. They include such operations as: sorting, separating, drying, transporting, and loading of silos with grain. For the rational using of these and other processes, it is necessary to take into account the possibility of interacting grains with each other and working devices of machines. This interaction depends on the nature of grain material movement both on the surfaces of working parts of the relevant equipment and in devices for performing secondary opera-tions connected with grain transportation to silo loading openings and the loading itself. Insufficient consid-eration of the peculiarities of grain flow movement can result in violating technological modes of elevator operating and, consequently, the quality of grain products stored in silos deteriorates. The technological process of loading silos with grain material, using open spiral loaders, takes place in the mode of rapid gravitation motion. A principal feature of this type of movement is the presence of conditions for rapid mov-ing of grains in grain layer. As a result of it, grains acquire a significant speed of chaotic movement. The work was aimed at identifying structural and kinematic characteristics of gravitation flows in an installation with discrete variable slope angles of acceleration and brake trays. The main tasks of the work were labora-tory study of wheat, corn and sunflower seed movement in U-shaped trays in order to establish the actual time of grain material movement in both the accelerator and brake trays. The trays were made of rolled steel, had the same length and roughness. Such studies using the gravitation installation are necessary to detect the rate of accelerating and breaking loose grain material of standard moisture content. It has been found that for the effective operation of the gravitation installation it is necessary that the inclination angle of the acceleration tray was much larger than the angle of the natural slope of grain material. Whereas, the inclination angle of the brake tray must be 1.22 times bigger than the angle of grain natural slope. Such ra-tio of angles makes it possible to obtain the movement of grain material in the brake tray at almost a con-stant linear speed, without a sharp increase in the mass and volume of grain load in this area.